Practical and social interaction justice of online learning during the COVID-19 pandemic - Rahmi Ramadhani; Dian Armanto; Fikry Prastya Syahputra; Titim Eliawati (International Journal of Evaluation and Research in Education (IJERE), 2023)
The implementation of learning in the current situation can be carried out using online learning as part of the methodology to answer the educational challenges caused by the outbreak of the COVID-19 pandemic. The role of technology in the online learning process in previous research studies has made it a major and important factor for successful learning in this emergency situation. This study aimed to investigate a philosophical perspective using the critical realism paradigm regarding the role of technology in online learning practices based on e-learning systems and justice in social interaction in aspects of learning implementation during the COVID-19 pandemic. This was a qualitative method with a critical realism approach. The results indicated that several critical arguments exist to rebalance the role of technology back to its origin, which is not a major factor, but a factor that still requires support from personal factors, personal behavior, and teacher readiness in facing technological developments. The findings of the study can be used to implement technology-based online learning while keeping practical and social justice in mind for both students and teachers.